Court-ship, Kinship and Business: A Study on the Interaction between the Formal and the Informal Institutions and Its Effect on Entrepreneurship - Tanika Chakraborty; Anirban Mukherjee; Sarani Saha (Institute for the Study of Labor (IZA), 2015)
In this paper we theoretically and empirically examine how the interaction between the formal court system and the informal loan network affects a household's decision to start a business. We find that when the formal court system is weak, expansion of informal credit network leads to the proliferation of business. However, with a sufficiently strong court system, expansion of credit network has a negative effect on business prospects. This result is explained by the contradictions between formal laws and norms used by informal networks. Our result remains robust after controlling for a variety of household and district level characteristics.
Keywords: K12; L26; O17; 330; informal network; court; formal institution; entrepreneurship